2013
DOI: 10.1080/19443994.2012.763049
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate removal from tail water by integrated vertical-flow constructed wetlands at a high hydraulic loading rate

Abstract: A B S T R A C TNitrate removal rates of two pilot-scale integrated vertical-flow constructed wetlands (IVCWs) treating tail water, under a hydraulic loading rate (HLR) of 250 mm/d with a mean influent NO À 3 -N concentration of 24.4 mg·L À1 , were evaluated. Mean NO À 3 -N removal efficiencies of 15.5 and 18.5% with mass removal rates of 1.01 g·m À2 ·d À1 and 1.16 g·m À2 ·d À1 for IVCW 1 (planted with Canna indica and Pontederia cordata) and 2 (planted with Typha orientalis and Arundo donax var. versicolor), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The pilot-scale IVCWs employed in this study have been depicted elsewhere [22,23]. Briefly, four parallel IVCWs, each composed of a sequence of a down-flow cell and another identical up-flow one, were constructed with bricks and concrete in a garden near the Donghu Lake, Wuhan, China (coordinates: 30˚33Ń , 114˚23´E; elevation: 27 m).…”
Section: Integrated Vertical-flow Constructed Wetlandsmentioning
confidence: 99%
“…The pilot-scale IVCWs employed in this study have been depicted elsewhere [22,23]. Briefly, four parallel IVCWs, each composed of a sequence of a down-flow cell and another identical up-flow one, were constructed with bricks and concrete in a garden near the Donghu Lake, Wuhan, China (coordinates: 30˚33Ń , 114˚23´E; elevation: 27 m).…”
Section: Integrated Vertical-flow Constructed Wetlandsmentioning
confidence: 99%
“…It was reported that NO 3 -N removal was only 7% in HFCW without carbon addition, but it increased to 70% when the COD/NO 3 -N ratio was maintained at 3.5:1 by the addition of sucrose. Similarly, in FSF CW complete NO 3 -N removal was observed when the COD/NO 3 -N ratio was between 3.5:1and 5:1, but further increase in C/N ratio did not increase the NO 3 -N removal (Chang et al 2013;Fang et al 2018). COD/NO 3 -N ratio below 2 limited the NO 3 -N removal because maximum organic matter removal took place in top layers of CW which reduced the carbon source for de-nitrification in bottom layers (Fang et al 2018) Another important parameter in CW is temperature since it affects the microbial community.…”
Section: Carbon/nitrogen Ratio and Temperaturementioning
confidence: 78%
“…Low C/N ratio wastewater is generally treated using anaerobic ammonium oxidation and simultaneous nitrification and de-nitrification but involves a huge amount of energy consumption (Li et al 2018). According to Chang et al (2013), carbon is an important parameter in NO 3 -N removal since it acts as an electron donor for the denitrification process. It was reported that NO 3 -N removal was only 7% in HFCW without carbon addition, but it increased to 70% when the COD/NO 3 -N ratio was maintained at 3.5:1 by the addition of sucrose.…”
Section: Carbon/nitrogen Ratio and Temperaturementioning
confidence: 99%